Physiotherapy in perimenopause: prevention, rehabilitation, and post-rehabilitation - Kljajić, Dragana M (Education and Research in Health Sciences, 2026)
Perimenopause represents a transitional phase in a woman’s life, commonly accompanied by physical and psychological symptoms resulting from declining and fluctuating estrogen levels. Musculoskeletal pain, reduced mobility, inflammatory processes, loss of muscle mass, and decreased bone density are among the key factors that may significantly impair daily functioning during the period preceding menopause.The aim of this paper is to present the role of physiotherapy in perimenopause through preventive, rehabilitative, and post-rehabilitative interventions that contribute to the preservation and improvement of functional capacities and the overall health status of women. The methodology is based on a narrative review of relevant literature published over the past 15 years, identified through electronic databases including PubMed, Google Scholar, KoBSON, and Scopus. The analysis indicates that preventive programs should integrate multimodal exercise approaches, including aerobic activities, strength training, stretching, and relaxation techniques, preferably implemented in small groups to ensure an individualized approach. Within the rehabilitative framework, physiotherapy plays a significant role in the prevention and management of conditions such as sarcopenia, osteoporosis, osteoarthritis, myofascial pain syndromes, greater trochanteric pain syndrome, and low back pain. Post-rehabilitation strategies focus on maintaining achieved outcomes, preventing symptom recurrence, and ensuring long-term preservation of musculoskeletal and psychophysical health. The findings highlight the importance of incorporating these contents into physiotherapy study programs and continuing professional education, with the aim of adequately preparing future therapists for evidence-based practice in women during perimenopause. In conclusion, physiotherapy represents an essential component of a multidisciplinary approach to health preservation in this demographic.
Keywords: perimenopause; symptoms; physiotherapy; prevention; rehabilitation; post-rehabilitation